Randomised crossover trial of rate responsive Activitrax and conventional fixed rate ventricular pacing. Issue 6 (December 1987) - Lipkin, D P; Buller, N; Frenneaux, M; Ludgate, L; Lowe, T; Webb, S C; Krikler, D M
Abstract : Atrial tracking pacemakers may improve exercise capacity and symptoms because they maintain atrioventricular synchrony and preserve the physiological response of heart rate to exercise. A rate responsive pacemaker which reacts to physical activity may be effective in patients with sinus node disease who are unsuitable for VDD pacing. At least three months after implant a double blind randomised short and long term crossover study was performed in ten patients with complete heart block: block was present at rest and during exercise on a modified Bruce protocol. Symptoms were assessed on a visual analogue scale and exercise capacity (maximal oxygen consumption and anaerobic threshold) was measured during rate responsive (peak rate 125/min) and conventional fixed rate (VVI) pacing (70/min). One month after randomisation treadmill exercise was performed. The mode was then changed to the other pacing mode and exercise was repeated three hours later. After another month the process was repeated but in the reverse order. During long term assessment there was subjective improvement in the sensation of breathlessness with rate responsive pacing. During short term assessment maximal oxygen consumption increased and the benefit was maintained during long term rate responsive compared with long term VVI pacing; oxygen consumption at the anaerobic threshold was similarly improved. Activity detecting rate responsive pacing is better than fixed rate ventricular pacing in patients with complete atrioventricular block.